Trees on Buildings: A Tree Selection Framework Based on Industry Best Practice - Majed Abuseif; Karine Dupre; Ruby N. Michael (Land, 2022)
Trees on buildings have received increased interest, and installations have multiplied over recent years, yet there is limited literature and policies guiding the successful implementation of projects relating to trees on buildings. This study investigates the tree selection process for implementation on buildings, using a survey and follow-up interviews with experienced experts to reveal current worldwide industry best practice, and provides a systematic framework for selecting the most appropriate tree species. A tree selection framework is proposed that consists of four stages: identifying the purpose of the tree; analysing the site context and its conditions; evaluating the risk of implementation; and investigating the characteristics of the candidate trees. Decision-makers can use the developed framework to inform design, implementation, and policy development of trees on buildings to reduce implementation risks. In addition, this paper provides useful insights to inform future research about trees on buildings.